EFFECT OF PROMOTION ON PURCHASE DECISION FOR E-TOLL CARD - Roinah Roinah; M. Rafid Marwal; Idarianty Idarianty; Dicky Jhon Anderson Butar Butar; Miftahorrozi Miftahorrozi (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2022)
The research objective is to analyze effect of promotion on purchase decision for e-toll card. The type of research conducted is causal (cause and effect). The population in this study are the users of the Jakarta–Cikampek Toll Road vehicles during 2020, which amounted to 138,365,987. This study also uses a snowball sampling technique. Hypothesis testing using simple regression analysis. The results show that promotion has a significant effect on purchase decision for e-toll card at the Jakarta–Cikampek Toll Road.